Influence of teacher’s subject matter knowledge on students ‘academic achievement of Kiswahili language in public secondary schools in Kathonzweni sub-county, KENYA - Kiamba, Elizabeth Welu; Mutua, Francis; Mulwa, David (My University, 2017)
Kathonzweni Sub County has been posting poor results in Kiswahili language. This prompted the researchers to undertake a study in the Sub County. The purpose of the study was to investigate the influence of teacher’s subject matter knowledge on students’ academic achievement in Kiswahili language. This study was guided by Teacher Efficacy theory. The study was conducted in Kathonzweni Sub County, Kenya. The target population comprised of 60 Kiswahili teachers and 39 principals in all the 39 public secondary schools in the Sub County. The sample size was all the 39 principals and 60 Kiswahili hence Census Survey. Questionnaires for principals and teachers were used as instruments of data collection. The objective of the study was; to establish the influence of teacher’s subject matter knowledge on students’ academic achievement in Kiswahili language in public secondary schools in the Sub County. Both questionnaires were piloted for reliability and yielded on Chronbach Alpha Coefficient of 0.833for principal’s questionnaire and 0.838 for teachers’ questionnaire. The data collected was quantitatively analyzed using Statistical package of Social Sciences (SPSS).Pearson Correlation was used to establish relationships. The findings established that; a teacher’s subject matter knowledge had significant influence on students’ achievement on Kiswahili language (r=0.618, p-value=0.000). The findings of the study may be useful in advising the Ministry of Education (MOE) on ensuring thorough grounding of teachers in teacher training colleges and universities to produce fully baked Kiswahili teachers.
Keywords: Kiswahili Language; Student Achievement; Subject Matter Knowledge; Teacher Preparedness